(Un)Making it in Rapture: The Critique of the Myth of the Self-Made Man, of Ayn Rand, and of Objectivism in BioShock (2007) and in BioShock: Rapture (2011) - Pereira, Teresa (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
This paper attempts to prove that BioShock (2007), a science fiction video game set in 1960, and BioShock: Rapture (2011), the novel published in its wake which starts in 1945, present a powerful critique of the myth of the self-made man, conveyed via the depiction of the fall of Rapture. Rapture is the dystopian, underwater city created by Andrew Ryan in which both the video game and the novel take place. The city is built in an art deco style reminiscent of the 1927 movie Metropolis. A Russian-born American tycoon, Ryan believed that nuclear annihilation was at hand and despised anything resembling socialist-like policies, which is why he decided to seclude himself and a few chosen ones somewhere underneath the Atlantic Ocean. The place he selected, Rapture, was based on Objectivism and closely related to Ayn Rand, an American-Russian writer who promoted an extreme version of individualism and laissez-faire capitalism, namely on one of her novels, entitled Atlas Shrugged (1957), in which she presents the capitalist utopia called Galt’s Gulch. Although they are never explicitly mentioned in the texts analysed here, both Rand and Galt’s Gulch provide Ryan and Rapture with their ethos, given that Ryan clearly resembles Rand and Rapture is strikingly similar to Galt’s Gulch. Despite promising that those willing to work hard enough would be able to fulfil the promises of the myth of the self-made man, Rapture ends up falling, largely because of its defence of Rand and Objectivist-inspired capitalist ideals, with the myth of the self-made man failing to be fulfilled. As a result, both the myth and, by extension, Rand and Objectivism, are called into question by BioShock and BioShock: Rapture, clearly located within the context of Cold War era and American culture and history.